Image of the world: from Antiquity to Modern times - Матвієнко, І. С.; Юхименко, А. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
The article deals with the problems of the world and the image of nature in the human mind and how we perceive the world, because it depends on the success of any society. In this article, we turn to the history of philosophical thought from Antiquity examining the interaction of nature and the world, going to the Middle Ages, where the problem is presented in three ways: world, nature, God, to the Renaissance , which appear utopia, as new plans for the development of the world and of Modern times, where there is a science that takes an entire ideological space era.